PHi-RACE: PGIMER in-house rapid & cost effective classifier for the detection of BCR-ABL1-like acute lymphoblastic leukaemia in Indian patients. Issue 3 (23rd February 2022) - Gupta, Dikshat Gopal; Varma, Neelam; Kumar, Ashish; Naseem, Shano; Sachdeva, Man Updesh Singh; Binota, Jogeshwar; Bose, Parveen; Gupta, Minakshi; Sonam, Preeti; Rana, Palak; Malhotra, Pankaj; Khadwal, Alka; et al.
Abstract: For the detection of BCR-ABL1 -like ALL cases, two methodologies, specifically Gene expression profiling (GEP) or Next-generation targeted sequencing (NGS) and TaqMan based low-density (TLDA) card, are being used. NGS is very costly and TLDA is not widely commercially available. In this study, we quantified the expression of 8 selected overexpressed genes in 536 B-ALL cases. We identified 26.67% (143/536) BCR-ABL1 -like ALLs using hierarchical clustering and principal component analysis. BCR-ABL1 -like ALL cases were significantly older at presentation ( p = 0.036) and had male preponderance ( p = 0.047) compared to BCR-ABL1 -negative ALL cases. MRD-positivity and induction failure were more commonest in BCR-ABL1 -like ALL cases (30.55 vs.19.35% in BCR-ABL1 -negative ALL cases). Lastly, we built a PHi-RACE classifier (sensitivity = 95.2%, specificity= 83.7%, AUC= 0.927) using logistic regression to detect BCR-ABL1 -like ALL cases promptly at diagnosis. This classifier is beneficial for hematologists in quick decision making at baseline to start tailored treatment regimes.